CHARACTERISTICS OF HUMAN RESOURCES NEEDED BY THE BANKING INDUSTRY IN MAKASSAR - Jibril, Nabila Mukmininah; Jibril, Hadira Thumaninah; Tajibu, Muhammad Jibril (Bisma: Jurnal Bisnis dan Manajemen, 2025)
This study aims to determine the characteristics of human resources (HR) that are needed by banks in recruiting employees. The study was conducted by distributing questionnaires to banks that were the research samples consisting of 10 banks, both conventional and sharia in Makassar. The questionnaire results were then processed using the Cochran Q test analysis tool, to determine the similarity of opinion among respondents regarding the indicators that are considered to be the characteristics of the required HR. Based on the analysis results, the criteria for human resources that are needed by the banking industry are having a high education, having a background in management and other sciences, having work experience or having an internship while studying, having computer and foreign language skills, communication skills, and having work discipline. The implication of this research is on the development of curriculum in higher education so that it is in line with the needs required in the banking industry, and so that college graduates can be absorbed. This research fills the gap by focusing on the specific HR attributes prioritized by  banks in Makassar, a topic that has received limited attention in previous studies.